Effectiveness of electronic patient reporting outcomes, by a digital telemonitoring platform, for prostate cancer care: the Protecty study - Helissey, C.; Parnot, C.; Rivière, C.; Duverger, C.; Schernberg, A.; Becherirat, S.; Picchi, H.; Le Roy, A.; Vuagnat, P.; Pristavu, R.; Vanquaethem, H.; Brureau, L. (Frontiers in Digital Health, 2023)
Research aim and purpose The benefits of Electronic Patient -Reported Outcomes (e-PRO) for telemonitoring are well established, allowing early detection of illnesses and continuous monitoring of patients. The primary objective of the PROTECTY study was to assess the compliance with patient use of the telemonitoring platform Cureety. An exploratory objective was to assess if the first-month health status is a prognostic factor of progression free-survival (PFS) and overall survival (OS) for prostate cancer patient. Methods This prospective study was conducted at the Military Hospital Bégin on prostate cancer patients. Patients were allowed to respond to a symptomatology questionnaire based on CTCAE v.5.0, personalized to their pathology and treatment. An algorithm evaluates the health status of the patient based on the reported adverse events, with a classification into 2 different states: Good Health Status (GHS) and Poor Health status (PHS). Results Sixty-one patients were enrolled between July 1st, 2020 and September 30th, 2021. The median age was 74.0 (range 58.0–94.0). 78% presented a metastatic stage, and the most represented cancer was mHSPC. Overall, 2,457 questionnaires were completed by the patients, 4.0% resulted in a health classification in to monitor or critical state. 87% of patients were classified in the GHS group. The compliance was 72% in the overall population during the first month, 71% in GHS group and 75% in PHS group. The median follow-up was 8 months. PFS at 6 months was 84% in GHS group vs. 57% in PHS group, p = 0.19. OS at 6 months was 98% in GHS group vs. 83% in PHS group, p = 0.31. Conclusions Our study showed that compliance was satisfactory. The feasibility of remote monitoring for prostate cancer patients means that they should benefit from its implementation. Our study is also the first to assess the correlation between treatment tolerance and survival. The initial results suggest that e-PRO assessment could help identify in the early stages the patients that require further health assessment and potential therapeutic changes. While further follow-up of more patients will be required, our study highlights the importance of e-PRO in cancer patient care.